Feasibility of Developing Direct Learning Models With a Life Based Learning Approach - Annita Kastur; Mustaji; Yatim Riyanto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study aims to analyze the feasibility of the results of the learning model instrument, textbooks, student worksheets, assessment sheets, and learning implementation plans. This study uses the Dick and Carey development model. There are 7 steps in Dick and Carey's learning, including 1) Identifying learning objectives, 2) Conducting learning analysis, 3) Analyzing student characteristics and learning context, 4) Formulating specific learning objectives, 5) Developing learning instruments, 6) Developing strategies learning, 7) Developing and selecting learning materials, 8) Designing and developing evaluation and assessment, 9) Revising learning programs, 10) Implementing and developing evaluations. Based on the results of the study showed that the research instruments in the form of the results of the learning model, textbooks, student worksheets, assessment sheets, and learning implementation plans scored good criteria. The direct learning model with a life-based learning approach is suitable for use as a learning model in improving student learning outcomes. This can be shown by the validity of the instrument.